Electrophoretic Deposition Of Cdse Nanoparticles Photoanode For Quantum Dots Sensitized Solar Cells - Ishak, Mohamad Nizam (2019)
CdSe nanoparticle was used as sensitizer in quantum dots sensitized solar cell (QDSSC). CdSe film was deposited on fluorine doped tin oxide (FTO) substrate by using electrophoretic deposition (EPD) as photoanode. The uniformity and coverage of CdSe film leading to improve efficiency and charge transfer of electron in QDSSC. In this research, two type of ligands were studied that were trioctylphosphine oxide (TOPO) and mercaptoundecanoic acid (MUA). TOPO capped CdSe nanoparticles were synthesized by hot injection method and using ligand exchange method to change TOPO capped CdSe to MUA capped CdSe. The purification process of CdSe nanoparticles solution was done with methanol to remove impurities. CdSe nanoparticles with diameter in the range of 2.27 nm to 3.36 nm were used for deposition of single layer and bi-layer of film. The applied voltage from 100 V to 400 V with deposition time of 5 minutes in chloroform solvent was used to deposit CdSe film on FTO by EPD. The CdSe/FTO was assembled with copper(II)sulfide (Cu2S) counter electrode and polysulfide electrolyte for I-V and electrochemical impedance spectroscopy (EIS) measurement for QDSSC. For single layer, the highest efficiency was recorded for CdSe/MUA (3.36 nm) of 0.132% with 195 Ω of Rct and the lowest efficiency was for CdSe/TOPO nanoparticle (2.27 nm) of 0.0164% with 15029 Ω of Rct. The combination of bi-layer for big/small (3.36/2.27 nm) CdSe/TOPO nanoparticles shown highest efficiency of 0.502% with 7258 Ω of Rct as compared to small/big (2.27/3.36 nm) particle that only have efficiency of 0.125% with 10153 Ω of Rct.